Perancangan Interior Café Co-Working Space di Surabaya - Wijaya, Kenny Ray; Honggowidjaja, Stephanus Pantja; Rizqy, Muhammad Taufan (Intra, 2019)
Co-Working Space Café is a place designed for visitors that come to the cafe could do their work or hanging out with their friends. So the visitors who come can increase their productivity and also be able to gather with their friends comfortably. The concept of this café is